1996
DOI: 10.1006/viro.1996.0401
|View full text |Cite
|
Sign up to set email alerts
|

Transcription, Translation, and Cellular Localization of ThreeAutographa californicaNuclear Polyhedrosis Virus Structural Proteins: ODV-E18, ODV-E35, and ODV-EC27

Abstract: This paper identifies two structural proteins of the occluded derived viral envelope of Autographa californica nuclear polyhedrosis virus (AcMNPV): ODV-E18 and ODV-E35. In addition, we identify a protein, ODV-EC27, that is incorporated into the capsid of occluded virus, which is not detected in budded virus. The genes for these proteins reside within the IE0 intron. The intron was sequenced, and five open reading frames (ORF) were identified. ORF 3 (genomic ORF 143) codes for the ODV envelope protein, ODV-E18.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 6 publications
(10 reference statements)
2
54
0
4
Order By: Relevance
“…According to the heptad repeat model (abcdefg) n in the TM helix of phospholamban, Leu 37 , Leu 44 , and Leu 51 occupy the a position and Ile 40 and Ile 47 occupy the d position in the motif; these residues create a leucine/isoleucine zipper (34,40). The leucine-and isoleucine-rich sequence 26 LYLLILFLV FIIVSPAII 43 in the TM helix of Ac76 shows similar characteristics, as L 26 and L 33 are localized to position a and L 29 , I 36 , and I 43 are localized to position d (Fig. 2E); thus, this sequence likely forms a hpt, the cells were incubated either with 20 g/ml digitonin for semipermeabilization or with 0.25% Triton X-100 for full permeabilization.…”
Section: Discussionmentioning
confidence: 99%
“…According to the heptad repeat model (abcdefg) n in the TM helix of phospholamban, Leu 37 , Leu 44 , and Leu 51 occupy the a position and Ile 40 and Ile 47 occupy the d position in the motif; these residues create a leucine/isoleucine zipper (34,40). The leucine-and isoleucine-rich sequence 26 LYLLILFLV FIIVSPAII 43 in the TM helix of Ac76 shows similar characteristics, as L 26 and L 33 are localized to position a and L 29 , I 36 , and I 43 are localized to position d (Fig. 2E); thus, this sequence likely forms a hpt, the cells were incubated either with 20 g/ml digitonin for semipermeabilization or with 0.25% Triton X-100 for full permeabilization.…”
Section: Discussionmentioning
confidence: 99%
“…ORF coding for this protein were detected on the genome of several members of the Baculoviridae family. ODV-E18 has been characterized as a late protein in AcMNPV that is associated with both the ODV envelope and capsid (Braunagel et al, 1996). The ORF number 12 on the ChfuGV genome potentially codes for a ODV-E18 homologue.…”
Section: Cforf2 a Homologue To Cporf2mentioning
confidence: 99%
“…Tel: 204-230-0210;Fax: 204-237-3240 E-mail: kiarashidan@juno.com al., 1996). The invaginated-inner nuclear membrane has been hypothesized to be the source of the baculovirus-induced intracellular microvesicles (Braunagel et al, 1996). It has been shown that one of the ODV-specific envelope proteins that can be found in these intracellular microvesicle structures is ODVP-6E/ODV-E56 (Braunagel et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Among these structural proteins, at least eight have been known to be specific to the ODV phenotype. These are as follows: VP17 (Funk and Consigli, 1993), ODV-E25 (Russell and Rohrmann, 1993), ODV-E35 (Braunagel et al, 1996), GP41 (Whitford and Faulkner, 1993), P74 (Kuzio et al, 1089), ODV-E18 (Braunagel et al, 1996), ODV-E66 (Hong et al, 1994), and ODVP-6E/ODV-E56 (Braunagel et al, 1996, Theilmann et al, 1996. The proteins that could participate in adsorption, fusion, and penetration have not been identified.…”
Section: Introductionmentioning
confidence: 99%